Immune gene expression in head and neck squamous cell carcinoma patients. (November 2019) - Lecerf, Charlotte; Kamal, Maud; Vacher, Sophie; Chemlali, Walid; Schnitzler, Anne; Morel, Claire; Dubot, Coraline; Jeannot, Emmanuelle; Meseure, Didier; Klijanienko, Jerzy; Mariani, Odette; Borcoman, Edith; et al.
Abstract: Background: Nivolumab and pembrolizumab targeting programmed cell death protein 1 (PD-1) have recently been approved among patients with recurrent and/or metastatic head and neck squamous cell carcinoma (HNSCC) who failed platinum therapy. We aimed to evaluate the prognostic value of selected immune gene expression in HNSCC. Patients and methods: We retrospectively assessed the expression of 46 immune-related genes and immune-cell subpopulation genes including immune checkpoints by real-time polymerase chain reaction among 96 patients with HNSCC who underwent primary surgery at Institut Curie between 1990 and 2006. Univariate and multivariate analyses were performed to assess the prognostic value of dysregulated genes. Results: The Median age of the population was 56 years [range: 35–78]. Primary tumour location was oral cavity (45%), oropharynx (21%), larynx (18%) and hypopharynx (17%). Twelve patients (13%) had an oropharyngeal human papillomavirus–positive tumour. Most significantly overexpressed immune-related genes were TNFRSF9 / 4- 1BB (77%), IDO1 (75%), TNFSF4 / OX40L (74%) and TNFRSF18 / GITR (74%), and immune-cell subpopulation gene was FOXP3 (62%). Eighty-five percent of tumours analysed overexpressed actionable immunity genes, including PD-1 / PD-L1, TIGIT, OX40 / OX40L and/or CTLA4 . Among the immune-related genes, high OX40L mRNA level (p = 0.0009) and low PD- 1 mRNA level (p = 0.004) were associated with the highest risk of recurrence. Among the immune-cell subpopulation genes, patients with high PDGFRB mRNA level (p < 0.0001) and low CD3E (p = 0.0009) or CD8A mRNA levels (p = 0.004) were also at the highest risk of recurrence. Conclusions: OX40L and PDGFRB overexpression was associated with poor outcomes, whereas PD-1 overexpression was associated with good prognosis in patients with HNSCC treated with primary surgery, suggesting their relevance as potential prognostic biomarkers and major therapeutic targets. Highlights: Most significantly overexpressed genes were 4- 1BB, IDO1, OX40L, GITR and FOXP3. Eighty-five percent of tumours overexpressed actionable genes such as PD-1 / PDL-1, TIGIT, OX40 / OX40L and/or CTLA4. High OX40L or PDGFRB mRNA level was associated with the highest risk of recurrence. Low PD-1 or CD3E or CD8A mRNA levels were associated with the highest risk of recurrence.